Mixing Tub and Washing Box for Finishing Work - Dharsono, Mulyadi Sugih (International Journal Labs, 2025)
This tool aims to reduce the impact of dirt arising from the finishing work of a building. The tool consists of two main parts: the dolak (mixing tub), which serves as a place to prepare the mixture, and the washing box (or washing tub), which is used for cleaning work equipment. By combining these two functions into one tool, the scattering of plaster or paint mixture can be avoided. With the presence of a stirring tub and washing box for finishing work, the cleanliness of the surrounding road environment can be maintained during the project implementation period. Dirty asphalt settling work can be eliminated, thus saving project costs. The project site will remain cleaner compared to when using cement mix, as the stirring tub is directly connected to clean water and the sewer system. Additionally, the mixture used will be more economical, as less is wasted. The use of this tool should be included in the Standard Operating Procedures (SOP) for finishing work to ensure that cleanliness in the project environment is consistently maintained.